Raman Spectroscopy Detects Amorphous Carbon in an Enigmatic Egg From the Upper Cretaceous Wido Volcanics of South Korea - Choi, Seung; Lee, Sung Keun; Kim, Noe-Heon; Kim, Seongyeong; Lee, Yuong-Nam (Frontiers in Earth Science, 2020)
Raman spectroscopy has been widely used in micropaleontology and organic geochemistry to identify carbonaceous materials and evaluate their thermal maturity in fossils or metasedimentary rocks. Meanwhile, fossil egg researches have mostly focused on biomineralized calcite, but preserved carbonaceous (or possibly organic) materials inside the eggshells have been usually neglected until recently. Here we report an enigmatic egg from the Wido Volcanics (Upper Cretaceous) of South Korea that was analyzed using diverse methods including polarized light microscope, scanning electron microscope, electron probe microanalyzer, electron backscatter diffraction, and Raman spectroscopy. The eggshell not only shows the crystallography of archosaurian eggshells but also contains peculiar dark bands, which were previously known as the trait of fossil and modern Crocodyliformes eggshells. Raman spectroscopic analysis showed that the dark bands are mainly due to amorphous carbon, as evidenced by the clear graphite (G) and disordered (D) bands. The deconvolution of amorphous carbon peaks and resultant parameters made it possible to infer the paleotemperature inscribed in the eggshell. The result suggests that preserved amorphous carbon in the fossil eggshells can be identified using Raman spectroscopy and Raman parameters may make it possible to compare the thermal maturity of spatiotemporally diverse fossil eggshells. The biogenicity of the dark band is not clear because Raman spectroscopic analysis is not sufficient to confirm biogenicity. However, overall distribution of the dark band may imply the biogenic origin. It is apparent that the material of this study is not a dinosaur egg but might belong to a crocodyliform or choristoderan egg, and even other non-dinosaur archosaur can be a candidate as well.